Hybrid Colloidal Plasmonic-Photonic Crystals - Romanov, Sergei G.; Korovin, Alexander V.; Regensburger, Alois; Peschel, Ulf (Advanced Materials, 2011)
We review the recently emerged class of hybrid metal-dielectric colloidal photonic crystals. The hybrid approach is understood as the combination of a dielectric photonic crystal with a continuous metal film. It allows to achieve a strong modification of the optical properties of photonic crystals by involving the light scattering at electronic excitations in the metal component into moulding of the light flow in series to the diffraction resonances occurring in the body of the photonic crystal. We consider different realizations of hybrid plasmonic-photonic crystals based on two- and three-dimensional colloidal photonic crystals in association with flat and corrugated metal films. In agreement with model calculations, different resonance phenomena determine the optical response of hybrid crystals leading to a broadly tuneable functionality of these crystals.
EAM Import::2019-03-13